PENGARUH FAKTOR PSIKOLOGI DAN SOSIAL BUDAYA TERHADAP KEPUTUSAN WISATAWAN BERWISATA DI TAMAN NASIONAL GUNUNG RINJANI - Rasid Ridha (Master of Management, Mataram University, 2016)
This study aimed to analyze the influence of psychological factors and socio-cultural factors ofthe tourists traveled decision on Mount Rinjani National Park. Respondent was done by usingpurposive sampling using a questionnaire distributed to 100 respondents. The data analysistechnique used is multiple linear regression analysis. Based on the analysis that has been done, it canbe concluded that psychological factors and socio-cultural factors a significant and positive influenceon the decision travelers traveled on Mount Rinjani National Park. This means that if psychologicalfactors and socio-cultural factors improved by the manager of the Mount Rinjani National Park, canimprove decision-traveled. While the dominant variable affecting traveled decision is socio-culturalfactors.Keywords: Psychological Factors, Socio-Cultural Factors, and Decision Travelling.